Nos bastidores do labirinto: estudo do processo de criação de Franklin Maxado - Santos, Érica Azevedo (2013)
The study of manuscripts provides a genetic perspective see the writer's struggle with language, through the movements of the creation process, as well as assists the reader and critic, to follow his course of genesis, to better understand the work. Each author has different processes of writing, as authors of the same period and the same language, for example, have different scriptures. examine the manuscripts of authors' work is one more method to a better understanding of the text and the author's style. And not only the manuscripts of writers devoted deserve to be investigated, but also those of the representatives of popular culture. It is, in this work, the study of the process of writing the bahian writer Franklin Maxado, from the analysis of the manuscripts of two of his pamphlets: It is forbidden to tell jokes or make such anecdotes and Confusion on the bus between an old and a student. In the backstage labyrinth: a study of the process of creating Maxado Franklin is the first work resulting from a research about the process of writing the cordel literature (string literature). For the organization of this research describes some of the areas of knowledge dealing with the study of the manuscript, with emphasis on methodological perspective used for this work, the Genetic Criticism. We also did a study on the life and work of Maxado: its artistic and professional path to learn and create your profile authorial assumptions about his creative process, through the movements present in writing manuscripts analyzed.